The Effect of Emotional Intelligence and Organizational Commitment on Organizational Citizenship Behavior (OCB) at Prasetya Bunda Hospital Tasikmalaya - Amzan Nur Alamsyah; Rita Tri Yusnita; Mila Karmila (Journal of Indonesian Management, 2023)
The purpose of this study was to find out and analyze the description of emotional intelligence, organizational commitment, and Organizational Citizenship Behavior (OCB) at Prasetya Bunda Tasikmalaya Hospital. The effect of emotional intelligence and organizational commitment simultaneously on Organizational Citizenship Behavior (OCB) of Prasetya Bunda Tasikmalaya Hospital. The effect of emotional intelligence partially on Organizational Citizenship Behavior (OCB) Prasetya Bunda Tasikmalaya Hospital. Partial influence of organizational commitment to Organizational Citizenship Behavior (OCB) of Prasetya Bunda Tasikmalaya Hospital. This research includes quantitative research in the sense that in this study it uses numbers, starting from data collection to interpreting data with statistical tests. The data collection technique used was a survey method. The data analysis technique used was descriptive statistical analysis and multiple linear regression tests. The results showed that emotional intelligence was in the very good category, organizational commitment was in the good category, and Organizational Citizenship Behavior (OCB) among Prasetya Bunda Tasikmalaya Hospital employees was in the good category. There is a significant simultaneous influence of emotional intelligence and organizational commitment to Organizational Citizenship Behavior (OCB) on Prasetya Bunda Tasikmalaya Hospital employees. There is a partial significant effect of emotional intelligence on Organizational Citizenship Behavior (OCB) in Prasetya Bunda Tasikmalaya Hospital employees. There is a partial significant effect of organizational commitment to Organizational Citizenship Behavior (OCB) on Prasetya Bunda Tasikmalaya Hospital employees.